2016
DOI: 10.1126/sciadv.1600584
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and aging

Abstract: Researchers review how random changes and our environment (for example, diet) determines our life span.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
548
1
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 671 publications
(580 citation statements)
references
References 231 publications
(315 reference statements)
13
548
1
18
Order By: Relevance
“…In addition, landmark observations in Caenorhabditis elegans have linked gain of H3K27me3 (and loss of the H3K27me3 demethylase UTX‐1) to extended longevity, strongly suggesting that preserving high levels of H3K27me3 by inhibiting KDM6/UTX may be critical for maintaining youthfulness (Jin et al., 2011; Maures et al., 2011; McCord et al., 2013; Shah et al., 2013). Despite conflicting data from different model systems, there is a trend for increases in activating histone marks (e.g., H3K4m2/3, H3K36me3) and decreases in repressive histone marks (e.g., H3K9m2/3, H3K27me3) indicative of a more actively transcribed genome, which is consistent with a well‐recognized open chromatin conformation in aging cells and organisms that culminates in the so‐called heterochromatin loss model of aging (Pal & Tyler, 2016). Metformin's ability to robustly restore the global levels of H3K27me3 in fibroblasts obtained from aged individuals or from patients with premature aging syndromes supports the notion that metformin could directly regulate the biological machinery of human aging by directly modifying aging‐associated histone mark changes and adds a new epigenetic dimension to the recent discovery of its capacity to alleviate the pathological defects of accelerated aging (Egesipe et al., 2016).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, landmark observations in Caenorhabditis elegans have linked gain of H3K27me3 (and loss of the H3K27me3 demethylase UTX‐1) to extended longevity, strongly suggesting that preserving high levels of H3K27me3 by inhibiting KDM6/UTX may be critical for maintaining youthfulness (Jin et al., 2011; Maures et al., 2011; McCord et al., 2013; Shah et al., 2013). Despite conflicting data from different model systems, there is a trend for increases in activating histone marks (e.g., H3K4m2/3, H3K36me3) and decreases in repressive histone marks (e.g., H3K9m2/3, H3K27me3) indicative of a more actively transcribed genome, which is consistent with a well‐recognized open chromatin conformation in aging cells and organisms that culminates in the so‐called heterochromatin loss model of aging (Pal & Tyler, 2016). Metformin's ability to robustly restore the global levels of H3K27me3 in fibroblasts obtained from aged individuals or from patients with premature aging syndromes supports the notion that metformin could directly regulate the biological machinery of human aging by directly modifying aging‐associated histone mark changes and adds a new epigenetic dimension to the recent discovery of its capacity to alleviate the pathological defects of accelerated aging (Egesipe et al., 2016).…”
Section: Discussionsupporting
confidence: 76%
“…To test the hypothesis that metformin might target the chromatin‐modifying activities of specific KDMs that actively remove well‐established aging‐related epigenetic changes (e.g., di‐ and trimethylation marks on histone H3 lysines 4, 9, 27, and 36; Pal & Tyler, 2016; Han & Brunet, 2012; Benayoun, Pollina & Brunet, 2015; Booth & Brunet, 2016), we first examined the global levels of several methylation marks, viz. H3K9me1, H3K9me3, H3K27me2, H3K36me3, H3K9me2, H3K27me3, and H3K4me3, in SV40‐immortalized mouse embryonic fibroblasts (MEFs).…”
Section: Resultsmentioning
confidence: 99%
“…A CpG-dinukleotidok globálisan nem gyakoriak, viszont bizonyos genomrégiókban, az úgynevezett CpG-szigetek területén igen nagy számban fordulnak elő [8]. A CpG-szigetek általában gének promóter szakaszában, illetve különböző regulátor régiói-ban találhatók [8] és többségében védettek a DNS-metilációval szemben [9]. A fejlődés során bizonyos promóter régiókban elhelyezkedő CpG-szigetek metilálttá válnak, így az általuk szabályozott gének nem fejeződnek ki [9] (2. ábra) [10,11] .…”
Section: A Dns-metiláció Funkciója Eukariótákbanunclassified
“…A promóter-metilációt megfigyelhetjük például az Xkromoszóma inaktivációja [12] vagy az imprinting jelensége esetén [13], illetve öregedés során is [9]. A CpG-szigeteken kívüli CpG-dinukleotidok általában az intergenikus régiókban, vagy a gének intronjaiban, így akár repetitív elemekben, transzpozonokban helyezkednek el [8].…”
Section: A Dns-metiláció Funkciója Eukariótákbanunclassified
“…Decreased expression of these genes has been shown to be associated with aging (32,33). Further experiments in the hiPSC-RPE lines showed that NAM can effectively decrease inflammatory cytokine production and repress the complement pathway, including C3.…”
mentioning
confidence: 98%